Tysiąc taktów tańca i muzyki. (Wejherowo : [wydawca nieznany], 1949)
Afisz informujący o występach 27.02.1949 r.
Keywords: Wejherowo (Polska) -- 1945-1970 -- druki ulotne; Wejherowo (Polska) -- 1945-1970 -- źródła